Frying of food oxidation, nutrient and non-nutrient antioxidants, biologically active compounds and high temperatures - Boskou, Dimitrios; Elmadfa, I. (CRC Press, 2011)
"This important resource concentrates mainly on two factors that influence the deterioration of a fat at elevated temperatures: the nature of the heated fat and the presence of oxidation retardants, especially those naturally occurring in oils or obtained from natural sources. Discussions include important biologically active ingredients present in oils and fats and minor constituents, which appear to affect the performance of a heated oil and/or may also be categorized as functional. Frying of Food also discusses olar phenolic compounds, which have an impact on the stability of oils at high temperatures"--